2019
DOI: 10.1007/s00292-019-0567-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymale und gemischte Uterustumoren

Abstract: Mesenchymale und gemischte Uterustumoren Aktuelle Übersicht und praktische Aspekte Im Bereich des Uterus können grundsätzlich alle mesenchymalen Tumoren vorkommen (. Tab. 1). Im Gegensatz zu den glattmuskulären Tumoren sind andere mesenchymale Tumoren aber sehr selten. Als Faustregel gilt, dass mehr als 90 % aller mesenchymalen Tumoren gutartig sind bzw. eine glattmuskuläre (leiomyogene) Differenzierung aufweisen. Die zweithäufigste Gruppe der mesenchymalen Uterustumoren, Tumoren des Endometriumstromas, sind e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…3,11 Rare cases of primary vulvovaginal low-grade endometrial stromal sarcoma (LGESS) have been reported, 32,33 and LGESS with fibromyxoid features may resemble LGFMS, 34 including rare cases of LGESS with collagen rosettes. 35 Highgrade endometrial stromal sarcoma with BCOR alterations may assume a multilobulated fibromyxoid appearance, 36 but these are primary to the uterus and show brisk mitoses and necrosis; vulvovaginal forms of BCOR-altered high-grade endometrial stromal sarcoma have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Rare cases of primary vulvovaginal low-grade endometrial stromal sarcoma (LGESS) have been reported, 32,33 and LGESS with fibromyxoid features may resemble LGFMS, 34 including rare cases of LGESS with collagen rosettes. 35 Highgrade endometrial stromal sarcoma with BCOR alterations may assume a multilobulated fibromyxoid appearance, 36 but these are primary to the uterus and show brisk mitoses and necrosis; vulvovaginal forms of BCOR-altered high-grade endometrial stromal sarcoma have not been described.…”
Section: Discussionmentioning
confidence: 99%